Manajemen Kearsipan dalam Meningkatkan Mutu Layanan Administrasi di Dinas Perpustakaan dan Kearsipan Kabupaten Aceh Tengah - Musradinur, Musradinur; Helmina, Helmina (Ta'dib: Jurnal Pemikiran Pendidikan, 2022)
Archives for organizations are supporting operational activities. Through archives, information and authentic can be obtained quickly and accurately. The organization's journey can be seen from the archived data stored. Therefore, good archives must be implemented, Realizing the importance of archives as a center of memory and a source of information. Service quality can be used as one of the agency's strategies to achieve customer satisfaction. This study aims to determine Archives Management in Improving the Quality of Administrative Services at the Library and Archives Service of Central Aceh Regency. This study uses a descriptive qualitative research approach. By using qualitative research, researchers can investigate archive management and archive service systems at the Central Aceh District Library and Archives Service. The results showed that archive management at the Central Aceh District Library and Archives Service had been going well, judging from the archival planning that had been running according to established procedures, the implementation of archives at the Central Aceh District Library and Archives Service could be said to be good, and supervision of The Central Aceh Regency Library and Archives Service is carried out twice a week, if an error occurs in the filing of the archive, it is quickly transferred to the specified place. The quality of archival services and the obstacles in improving the quality of archival services at the Central Aceh Regency Library and Archives Service can be said to be still not optimal due to the lack of available reading media such as historical books and digital services such as wifi networks that cannot be reached by the archives and so it is difficult to upgrade and upload the latest info or activities.